Pooled genomic indexing of rhesus macaque - Milosavljevic, Aleksandar; Harris, Ronald A.; Sodergren, Erica J.; Jackson, Andrew R.; Kalafus, Ken J.; Hodgson, Anne; Cree, Andrew; Dai, Weilie; Csuros, Miklos; Zhu, Baoli; de Jong, Pieter J.; Weinstock, George M.; et al. (Genome Research, 2005)
Pooled genomic indexing (PGI) is a method for mapping collections of bacterial artificial chromosome (BAC) clones between species by using a combination of clone pooling and DNA sequencing. PGI has been used to map a total of 3858 BAC clones covering ∼24% of the rhesus macaque (Macaca mulatta) genome onto 4178 homologous loci in the human genome. A number of intrachromosomal rearrangements were detected by mapping multiple segments within the individual rhesus BACs onto multiple disjoined loci in the human genome. Transversal pooling designs involving shuffled BAC arrays were employed for robust mapping even with modest DNA sequence read coverage. A further innovation, short-tag pooled genomic indexing (ST-PGI), was also introduced to further improve the economy of mapping by sequencing multiple, short, mapable tags within a single sequencing reaction.
10.1101/gr.3162505